Scanning-tunneling-microscopy study on the growth mode of vapor-deposited gold films - Herrasti, Pilar (1992)
The growth of gold deposits on smooth glass from the vapor phase at 30 nm−1 s −1, 298 K, and incident angle near the substrate normal covering the 30—1000 nm average film thickness (h¯) range is investigated through scanning tunneling microscopy (STM) complemented with oxygen-adatom electrosorption measurements. The STM images of the deposits reveal a columnar structure resulting from a mechanism involving shadowing and surface diffusion. Quantitative data are obtained directly from STM images. The height distribution N(h) of the interface obeys an N(h)∝ e −kh relationship. For h¯<500 nm, the interface thickness (ξ) increases as a power law with h¯, whereas for h¯ > 500 nm it reaches a steady state. Under the latter condition, ξ depends on the STM scan length (S) as ξ∝ Sα with a close to 1/3. These results indicate that the growth process of the gold deposits results in compact nonfractal structures with self-affine fractal surfaces, as predicted by ballistic deposition models. However, the latter fail to describe some aspects of the morphology and evolution of thin vapor-deposited gold films on this substrate.